Tetrameric Oligomerization of IκB Kinase γ (IKKγ) Is Obligatory for IKK Complex Activity and NF-κB Activation - Tegethoff, Sebastian (American Society for Microbiology, 2003)
The IκB kinase (IKK) complex mediates activation of transcription factor NF-κB by phosphorylation of IκB proteins. Its catalytic subunits, IKKα and IKKβ, require association with the regulatory IKKγ (NEMO) component to gain full basal and inducible kinase activity. However, the oligomeric composition of the IKK complex and its regulation by IKKγ are poorly understood. We show here that IKKγ predominantly forms tetramers and interacts with IKKα or IKKβ in this state. We propose that tetramerization is accomplished by a prerequisite dimerization through a C-terminal coiled-coil minimal oligomerization domain (MOD). This is followed by dimerization of the dimers with their N-terminal sequences. Tetrameric IKKγ sequesters four kinase molecules, yielding a γ(4)(α/β)(4) stoichiometry. Deletion of the MOD leads to loss of tetramerization and of phosphorylation of IKKβ and IKKγ, although the kinase can still interact with the resultant IKKγ monomers and dimers. Likewise, MOD-mediated IKKγ tetramerization is required to enhance IKKβ kinase activity when overexpressed in 293 cells and to reconstitute a lipopolysaccharide-responsive IKK complex in pre-B cells. These data thus suggest that IKKγ tetramerization enforces a spatial positioning of two kinase dimers to facilitate transautophosphorylation and activation.